Mechanisms involved in thermal degradation of lignocellulosic fibers: a survey based on chemical composition - Ornaghi, Heitor L. [UNESP]; Ornaghi, Felipe G.; Neves, Roberta M.; Monticeli, Francisco [UNESP]; Bianchi, Otávio (Springer Nature, 2020)
The aim of this study was to determine the Arrhenius parameters and degradation mechanism for each component of biomass, including extractives, water, hemicellulose, cellulose and lignin. A statistical tool (F-test) was used as well as simulations of the effects of each component and the respective chars formed during thermal degradation. Experimental and theoretical curves for each component were simultaneously fitted, and the influence on the final thermal degradation curve was evaluated. Simulation of the TG curve was based on recently published models, for which one, two and three-step mechanisms were tested to complete the statistical evaluation. The activation energy showed a dependence on the cellulose and the reaction order on the hemicellulose polymer structures. On the other hand, lignin is the most complex material in biomass and thus a broader range of degradation mechanisms is associated with its char and this plays a significant role in the final “tail” of the TG curve. In the case of cellulose and hemicellulose, autocatalysis is the most probable degradation mechanism while for the respective chars it is diffusion. The char formation significantly increases the activation energy. The results of this study provide an insight into the chemistry involved in the pyrolysis of multicomponent biomass, which will facilitate the building of a prediction model.
Keywords: Lignocellulosic; Model-fitting; Modeling and simulation; Pyrolysis; Thermal decomposition